2010
DOI: 10.1002/imhj.20268
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive perspectives in language outcomes of Early Head Start: Language and cognitive stimulation and maternal depression

Abstract: A neurocognitive, developmental framework was used to examine the effectiveness of Early Head Start (EHS) programs. Evidence has shown that caregiver variables impact early brain development. This study aimed to better understand this relation. Results showed that the EHS program made no significant impact, and at 3 years old, children were significantly behind population norms in language development, partially replicating previous findings with children from poverty backgrounds. EHS and parental depression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…91 Parental depression, also elevated in low-SES families, additionally contributes to profiles of input, 84 and has been independently associated with lower language outcomes in children. [92][93][94] Poorer households may also be characterized by disorganization in the nature of everyday activities that influence the quality of parentchild verbal interaction, 95 and lower-income parents are more likely to have their children in lower-quality child care and preschool settings. 57,96,97 On a more positive note, intervention programs and counseling parents on the types of verbal interactions that help children learn language have good documented outcomes.…”
Section: Children In Families Of Low Socioeconomic Statusmentioning
confidence: 99%
“…91 Parental depression, also elevated in low-SES families, additionally contributes to profiles of input, 84 and has been independently associated with lower language outcomes in children. [92][93][94] Poorer households may also be characterized by disorganization in the nature of everyday activities that influence the quality of parentchild verbal interaction, 95 and lower-income parents are more likely to have their children in lower-quality child care and preschool settings. 57,96,97 On a more positive note, intervention programs and counseling parents on the types of verbal interactions that help children learn language have good documented outcomes.…”
Section: Children In Families Of Low Socioeconomic Statusmentioning
confidence: 99%
“…Children's development and school readiness are related to their home and early care and education environments. Researchers have found that maternal education (Bracken & Fischel, 2008) and depression (Chapin & Altenhofen, 2010), home environments (Chazan-Cohen et al, 2009;Krishnakumar & Black, 2002), home language (Lee & Burkam, 2002), family income (Lee, 2005;Lee & Burkam, 2002), minority status (Panter & Bracken, 2009), and early care and education experiences (Love et al, 2003;National Institute of Child Health and Human Development Early Child Care Research Network, 2002) predict children's development and school readiness. In the current study, these variables are considered as possible covariates when examining children's school readiness.…”
Section: O T H E R F a C T O R S R E L A T E D T O S C H O O L R E A D I N E S Smentioning
confidence: 99%
“…Though the disability associated with depression is well documented (McQuaid, Stein, Laffaye, & McCahill, 1999; Moussavi et al, 2007), some of the greatest costs of depressive conditions are those borne by the children of depressed mothers. Children of women with depressive syndromes are at increased risk for both internalizing and externalizing difficulties (Goodman, Lamping, & Ploubidis, 2010) as well as for impairments in cognitive and language development (Chapin & Altenhofen, 2010; Cycyk, Bitetti, & Hammer, 2015). The intergenerational transmission of psychopathology appears to be attributable, in part, to environmental influences associated with depressive symptomatology (Hummel & Kiel, 2015; Natsuaki et al, 2014; Radke-Yarrow & Klimes-Dougan, 2002).…”
Section: Mom-net: Evaluation Of An Internet-facilitated Cognitive Behmentioning
confidence: 99%